Closure of oroantral communications with Bichat´s buccal fat pad. Level of patient satisfaction - Alonso-González, Rocío (J Clin Exp Dent, 2015)
Purpose: To report the closure of oroantral communications with the pedicled buccal fat pad in a series of patients, and to determine the level of patient satisfaction after the surgery. Study Design: A prospective study of patients diagnosed of unilateral or bilateral oroantral communication (OAC) closed using the buccal fat pad between May 2012 and January 2013 was performed. Data analysis extended to: age, sex, and cause, location and size of oroantral communication. Complications and success related to buccal fat pad surgery were evaluated. Also, patient satisfaction was assessed after six months of surgery. Results: Nine patients (3 men and 6 women) with a mean age of 50.5 years and 11 OAC treated with buccal fat pads were included. The most common cause of oroantral communication was the extraction of molars. The average widest diameter of the oroantral communication was 7.1 mm. One week after the surgeries no complications were found. One month after surgery, one patient presented persistence of the oroantral communication; in this patient, the buccal fat pad technique was considered a failure, and a second intervention was performed using a buccal mucoperiosteal flap to achieve primary closure of soft tissues. After six months, patient showed closure of the communication and complete healing. All the other communications had been solved with Bichat´s ball technique, yielding a success rate of 90.9%. Mean patient overall satisfaction was 9.1 out of 10; patients were satisfied with phonetics (9.4), aesthetics (9) and chewing (9). Conclusions: The buccal fat pad technique was successful in closing 10 out of 11 oroantral communications and few complications were found. Patients were highly satisfied in overall with the treatment and with phonetics, aesthetics and chewing. Key words:Bichat’s fat pad, buccal fat pad, oroantral communication.